Sales Application Program at Palinggihan Restaurant in Kuningan - Abi Surya Wijaya (Politeknik Siber Cerdika Internasional, 2021)
The culinary business has good prospects and is one of the growing business opportunities today, ranging from traditional food traders with the term street vendors, buffets to modern food traders who claim to be cafe and restaurant entrepreneurs. The purpose of this study is to determine the effective sales application program used in a business. To collect data to meet the preparation of this application program, the authors do several ways, namely. Observing the service process at the restaurant by becoming a buyer, experiencing firsthand how the service at the Palinggihan Restaurant is by collecting data and obtaining data that will be used as writing material. Conducting direct interviews with employees of the fragrant sweet restaurant about sales activities and transactions at the fragrant sweet restaurant by asking various questions to obtain information and data